Custos de lajes formadas por vigotas treliçadas considerando a produção, o transporte, a montagem e a concretagem - Forni, Daniel (2005)
The use of slabs formed by prefabricated elements in structures of pavements becomes more and more spread in the Brazilian market, mainly lattice reinforced joists. This work purposes to analyze the costs involved in the production process of lattice reinforced joists, during transport, assembly and slab casting. The cost _expression obtained was analyzed in some numerical examples of concrete slabs (one and two-way) with several dimensions. The cost was also evaluated by the method of optimization of generic gradient (GRG) for ceramic and EPS infill blocks. The design variables considered for cost minimization were the height and the resistance of the concrete layer. For slabs with EPS the distance between lattice reinforcement joists was also considered. The final cost of slabs with ceramic blocks had an economy around 4%, which was close to 8% for slabs formed with EPS. In these slabs (EPS), larger values for the distance between lattices reinforcement joists were obtained, which resulted in smaller concrete volume and smaller number of lattice joists. The variation of more or less 40% was considered in the cost of the concrete and the reinforcement in order to evaluate their effect in the final cost. In slabs with ceramic blocks, around 12% of increase and decrease in the final cost was observed. The final cost of slabs with EPS (which distance between lattices reinforcement joists was optimized) was close to 8% for variations in the price of the concrete and from 6 to 11% for variations in the price of the reinforcement.